Analsisis Kepatuhan Minum Obat Pada Lansia Hipertensi di Puskesmas Pengandonan Kota Pagar Alam - Dina Fitriananci; Lilis Suryani; Yusnilasari (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
Hypertension is an increase in blood pressure that can trigger strokes, kidney disease and heart attacks. To reduce the risk of cardiovascular disease that can be triggered by hypertension by taking antihypertensive drugs adequately. The purpose of this study was to look at the factors associated with medication adherence in hypertensive patients. This study uses a quantitative method with a Cross Sectional approach. Statistical test using Chi Square test. Multivariate analysis in this study used multiple logistic regression analysis. In this study, it can be concluded that there is a relationship between age (p value = 0.005), knowledge (p value = 0.011); and family support (p value = 0.012) with medication adherence. There is no relationship between gender (p value = 0.557) and the role of officers (p value = 0.260) with medication adherence in hypertension patients in the UPTD area of Pengandonan Health Center Kec. Pagar Alam Utara Pagar Alam City in 2021. Suggestions for puskesmas should the Puskesmas optimize service programs related to elderly services such as posyandu for the elderly. As for the next research should examine the incidence of hypertension with different research methods and designs.